AB0208 Immune complex formation after exposure of autoantigens on the surface of secondary necrotic cells (SNEC) promotes inflammation in SLE. (23rd January 2014) - Munoz, L.E.; Janko, C.; Franz, S.; Siebig, S.; van der Vlag, J.; Schett, G.; Herrmann, M.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is a chronic inflammatory disease characterised by the production of autoantibodies, formation of immune complexes (IC), and activation of complement.[1] Accumulation in blood and tissues of post-apoptotic remnants is considered of etiological and pathological importance for patients with SLE.[2, 3] Objectives: The goal of this work is to analyse the phenotype of non-cleared remnants of apoptotic cells are to test if this phenotype contributes to the induction of inflammatory responses in SLE. Methods: SNEC were generated by UVB irradiation of human lymphocytes followed by incubation for 48 hours. We employed fluorescence microscopy, FACS, and an ex vivo phagocytosis assays to demonstrate the availability of autoantigens on the surface of SNEC to form immune complexes that provoke inflammation. Results: We describe the exposure of dsDNA on the surface of SNEC and the binding of serum opsonins to the surface of SNEC. We show that anti-dsDNA and other autoantibodies bind and sensitise SNEC. Autoantibody-sensitised SNEC were cleared by macrophages in vitro and induced a pro-inflammatory cytokine response. Conclusions: Lupus autoantigens are exposed on the surface of SNEC and available to assemble intricate immune complexes with various autoantibodies. The clearance of cellular remnants that are not properly removed from the organism is targeted by lupus autoantibodies causing systemic inflammation in some patients with SLE. References: Hahn, BH, Overview of pathogenesis of Systemic Lupus Erythematosus, in: Dubois' Lupus Erythematosus, D.J. Wallace and B.H. Hahn, Editors. 2007, Lippincott Williams & Wilkins: Philadelphia. p. 1414. Munoz, LE, Janko, C, Grossmayer, GE, Frey, B, Voll, RE, Kern, P, Kalden, JR, Schett, G, Fietkau, R, Herrmann, M, and Gaipl, US, Remnants of secondarily necrotic cells fuel inflammation in systemic lupus erythematosus. Arthritis Rheum 2009;60:1733-42. Munoz, LE, Lauber, K, Schiller, M, Manfredi, AA, and Herrmann, M, The role of defective clearance of apoptotic cells in systemic autoimmunity. Nat Rev Rheumatol 2010;6:280-9. Disclosure of Interest: None Declared